Representasi Gender dalam Film Dua Garis Biru (2019) - Harigelita, Dian; Tandian, Erina Adeline; Sari, Nia (Urban: Jurnal Seni Urban, 2019)
The Indonesian film, Two Blue Stripes (2019), narrates the story of a teenage couple who gets pregnant out of wedlock. The protagonists of this film are Bima and Dara, who come from different backgrounds. Bima is responsible for Dara’s pregnancy. There are several gender discourses based on Indonesian culture, especially in the setting of Jakarta, which this film tries to convey. This article aims to examine gender representation in the film Two Blue Stripes. The research method is textual study by observing the mise-en-scene in the film. The approach is cultural studies with a focus on gender issues. The results of the study state that the representation of patriarchal mindset, which is conveyed in this film, does not only hurt Dara as a female character, but also Bima as a male character as well.Film Indonesia berjudul Dua Garis Biru (2019) menceritakan tentang pasangan remaja yang hamil di luar nikah. Protagonis film ini adalah Bima dan Dara yang memiliki latar belakang berbeda. Bima memutuskan bertanggung jawab atas kehamilan Dara. Ada beberapa wacana gender berdasarkan budaya Indonesia, terutama dengan latar Jakarta, yang coba disampaikan dalam film ini. Artikel ini bertujuan mengkaji representasi gender dalam film Dua Garis Biru. Metode penelitian yang dilakukan adalah kajian tekstual dengan mengamati mise-en-scene film. Pendekatan yang dilakukan yaitu cultural studies dengan berfokus pada masalah gender. Hasil kajian menyatakan bahwa representasi pemahaman patriarki, yang disampaikan dalam film ini, tidak hanya merugikan tokoh Dara sebagai perempuan saja, namun juga Bima sebagai tokoh laki-laki.